SYSTEMATIC LITERATURE REVIEW: WILLINGNESS TO PAY FOR CONSUMERS TO ORGANIC RICE - Barki, Khotimatul; Rachmah, Malinda Aptika (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: Organic rice is a food product that is cultivated organically, does not contain chemicals and pesticides, and has a high nutrient and antioxidant content. This study aims to 1) find out the method used to collect data about consumers' willingness to pay for organic rice, 2) find out the method used to measure the level of willingness to pay for organic rice, 3) find out the factors that influence consumers' willingness to pay for organic rice. Methods: The method used in this study is the SLR (Systematic Literature Review) method with PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis). Results: The results showed that 1) the highest frequency in data collection techniques was carried out using questionnaires and interviews (460 respondents), 2) the highest frequency in data analysis was using the CVM (contingent valuation method), 3) the most frequent category of factors influencing WTP, namely price product. Conclusion and suggestion: The more research questions answered in published journals, the more data collection methods, methods of measuring WTP, and factors that influence WTP are often used in research.